Identification of hub genes associated with follicle development in multiple births sheep by WGCNA - Wang, Jinglei; Chen, Hanying; Zeng, Xiancun (Frontiers in Veterinary Science, 2022)
Sheep exhibit a distinct estrous cycle that includes four different phases: proestrus, estrus, late estrus, and luteal phase. As the estrous cycle repeats, follicular development regularly alternates. We thus investigated ovarian transcriptome data from each of the four phases using weighted gene co-expression network analysis (WGCNA) to identify modules, pathways, and genes essential to follicle growth and development. We clustered mRNA and long non-coding RNA (lncRNA) into different modules by WGCNA, and calculated correlation coefficients between genes and Stages of the estrous cycle. Co-expression of the black module (cor = 0.81, P<0.001) and the yellow module (cor = 0.61, P<0.04) was found to be critical for follicle growth and development. A total of 2066 genes comprising the black and yellow modules was used for functional enrichment. The results reveal that these genes are mainly enriched in Cell cycle, PI3K-Akt signaling pathway, Oocyte meiosis, Apoptosis, and other important signaling pathways. We also identified seven hub genes (BUB1B, MAD2L1, ASPM, HSD3B1, WDHD1, CENPA, and MXI1) that may play a role in follicle development. Our study may provide several important new markers allowing in depth exploration of the genetic basis for multiparous reproduction in sheep.